The Fund's Capacity Development Strategy : Better Policies Through Stronger Institutions. (Policy Papers; Policy Paper, 2013)
This paper outlines reforms to increase the effectiveness of the Fund's capacity development (CD) program. It builds on the 2008 and 2011 reviews of technical assistance (TA) and the 2008 review of training, which set in motion important changes to make CD more valuable to member countries. Reforms will involve Board endorsement in a few areas and implementation by staff of related next steps.